Did Elijah Show Respect to Royalty? - Kadari, Adiel (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2015)
At the end of the description of the dramatic event at Mount Carmel, Kings relates that after the heavy downpour began Elijah ran before the king to Jezreel. Elijah’s running was already understood in the Tannaitic sources as a gesture meant to show respect to royalty. This interpretation, which is not consistent with the characterization of Elijah as zealous that emerges from the biblical narrative, was accepted by both medieval and modern biblical commentators. The article discusses this interpretive tradition in its textual and historical contexts and reveals the conceptual stance that it expresses. At the center of the discussion is a passage from Mekilta de-Rabbi Ishmael, in which this interpretive tradition first appears. The article indicates a number of strata in the Mekilta text, each of which expresses a different ideological approach to the question of the proper attitude to “royalty.” The article proposes that Mekilta reflects different positions on the question of the proper attitude to the Roman authorities, and reveals an ideological-educational conflict over the image and heritage of biblical characters as part of the struggle over the fashioning of the collective Jewish historical and political memory.